Assessment of Political Principles in the Constitution of Oman from International Law Perspectives - Al Aghbari, Fahad; Hassan, Muhamad Sayuti; Musa, Nurhafilah (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
The Constitution of the Sultanate of Oman incorporates several political principles that guide the state’s policy in international relations, including non-interference in internal affairs, adherence to international treaties, and observance of customary international law. The significance of this research lies in assessing the compatibility of these constitutional principles with international law. This study adopts a descriptive-analytical approach to examine these principles. Additionally, it compares the application of international law by various states and the rulings issued by international judicial bodies.The primary objective of this paper is to evaluate the extent to which the political principles enshrined in the Omani Constitution align with the principles of public international law, while also identifying the challenges associated with their domestic implementation. The findings indicate that these principles have played a crucial role in enhancing Oman’s international reputation and fostering positive relations with various countries and international organizations.Finally, this paper presents several recommendations to address the challenges related to the application of these principles. The study concludes that Oman’s adherence to these principles has facilitated the effective implementation of international law. However, it also highlights the need to address specific challenges concerning the application of international treaties and conventions.